Grammaticalization of Arabic prepositions and subordinators : a corpus-based study - Esseesy, Mohssen (Studies in Semitic languages and linguistics ;, 2010)
The empirical findings of this study establish that prepositions remain central to Arabic language users. It shows that they utilize them for construction of phrases, linked clauses, and organization of discourse, among other notable functions.